2022
DOI: 10.1002/anie.202213429
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Tetraarylethenes: Universal Tags for the Synthesis of Solid State Luminogens

Abstract: The aggregation-induced emission properties of tetraarylethenes (TAEs) have led to numerous applications in chemistry, biology, and materials science. Herein, we describe two fluorinated tetraarylethenes, which can be employed as universal tags for the synthesis of solid state luminogens. The tags are accessible in one or two steps from commercially available starting materials. Facile coupling reactions with ubiquitous substrates such as thiols, alcohols, amines, phosphines, aldehydes, and enamines allow prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…In all the cases, the transformations occurred at the para position of the pentafluorophenyl functionality in 3a under mild conditions, demonstrating a selectively nucleophilic substitution pathway. 22 By employing different bases, solvents, and temperatures, product 3a bearing a reactive C 6 F 5 functionality could readily undergo chemoselective coupling with NaN 3 , pyrazole, 4-methylbenzenethiol, 23 and NaBH 4 , 24 yielding perfluoroarylated compounds 5 (88%), 6 (87%), 7 (64%) and 4m (86%), respectively. Perfluoroaryl azide 5 can be promising for synthetically useful purpose in organic synthesis as the C 6 F 4 N 3 moiety can be used for conjugation reactions with phosphines, aldehydes and enamines, and also for C–H functionalization of inert polyolefins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In all the cases, the transformations occurred at the para position of the pentafluorophenyl functionality in 3a under mild conditions, demonstrating a selectively nucleophilic substitution pathway. 22 By employing different bases, solvents, and temperatures, product 3a bearing a reactive C 6 F 5 functionality could readily undergo chemoselective coupling with NaN 3 , pyrazole, 4-methylbenzenethiol, 23 and NaBH 4 , 24 yielding perfluoroarylated compounds 5 (88%), 6 (87%), 7 (64%) and 4m (86%), respectively. Perfluoroaryl azide 5 can be promising for synthetically useful purpose in organic synthesis as the C 6 F 4 N 3 moiety can be used for conjugation reactions with phosphines, aldehydes and enamines, and also for C–H functionalization of inert polyolefins.…”
Section: Resultsmentioning
confidence: 99%
“…Perfluoroaryl azide 5 can be promising for synthetically useful purpose in organic synthesis as the C 6 F 4 N 3 moiety can be used for conjugation reactions with phosphines, aldehydes and enamines, and also for C–H functionalization of inert polyolefins. 17 a ,23 Compound 4m as a monoalkenylated polyfluoroarene substrate could further react with alkene 1a to give divinylated perfluorobenzene 4m′ in 86% yield (see the ESI† for details).…”
Section: Resultsmentioning
confidence: 99%
“…They are also key precursors for various useful transformations such as hydrogenation, epoxidation, reductive Heck and other processes that generate contiguous highly substituted C(sp 3 ) centers 3 . The importance of such tetrasubstituted olefins in both academia and industry has stimulated the enduring efforts towards exploiting the catalytic methods for their syntheses [4][5][6][7][8][9][10][11][12] . In this context, the transition metal-catalyzed difunctionalization of alkynes via carbometallation stands for the most efficient and modular route to synthesize fully substituted olefins 3,[13][14][15][16][17][18][19][20][21][22] , but still suffers from the difficulty in achieving regio-/stereocontrol when applied to electronically or sterically unbiased substrates.…”
mentioning
confidence: 99%
“…8,9 Symmetric tetrasubstituted alkenes are conveniently synthesized via McMurry's coupling of diarylketones by low-valent titanium, which are inefficient for the preparation of unsymmetrical species due to the competing homocoupling reactions (Scheme 1a). 10,11 The most common approach toward unsymmetrical tetrasubstituted alkenes typically relied upon Rathore's dehydration of tertiary alcohols (Scheme 1b), 12,13 Severin's vinylation of arenes (Scheme 1c) 14,15 and classic Suzuki cross-coupling of triphenylethenyl bromide with arylboronic acids. 16,17 Despite the large synthetic utility of these methods, the requirement of highly sensitive organometallic reagent (lithium, magnesium, etc.…”
mentioning
confidence: 99%
“…It has been shown that compounds with aggregation-induced emission (AIE) properties have enormous potential applications in materials sciences, chemical sensing, organic light-emitting diodes (OLEDs), and biological probes. Tetrasubstituted alkenes have been established as prototypical AIE luminogens (AIEgens) in this context. , Symmetric tetrasubstituted alkenes are conveniently synthesized via McMurry’s coupling of diarylketones by low-valent titanium, which are inefficient for the preparation of unsymmetrical species due to the competing homocoupling reactions (Scheme a). , The most common approach toward unsymmetrical tetrasubstituted alkenes typically relied upon Rathore’s dehydration of tertiary alcohols (Scheme b), , Severin’s vinylation of arenes (Scheme c) , and classic Suzuki cross-coupling of triphenylethenyl bromide with arylboronic acids. , Despite the large synthetic utility of these methods, the requirement of highly sensitive organometallic reagent (lithium, magnesium, etc. ), specialized starting materials, and multistep operations severely limit the reaction generality in terms of functional group tolerance and substrate availability.…”
mentioning
confidence: 99%